(3QSGdI aj GdMceIs - (3CQSWh aQbhQjhSs
(3ChdgG (B:s
(3djSJ CcKQ ef GdYde fXGe GdehLhOGJ hfXGe GdehLhOGJ ehLhO aGdadSaI ehLhOI s
(3BNQgG (B:s
(3jchf ef eNGQb hGdNGUg djS hgfG jbWY aQbhQjhS GdcdGe s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(1561) s
Keywords: (3GdadSaI hGdefWbs